2016
DOI: 10.1111/jdi.12522
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and the risk of cancer incidence in patients with type 2 diabetes in Japan: Results from the National Center Diabetes Database

Abstract: Aims/IntroductionBoth type 2 diabetes and obesity increase the risk of some types of cancers, and underlying mechanisms are thought to be, at least in part, common. In the present study, we carried out a retrospective cohort study of the relationship between body mass index (BMI) categories and cancer development in Japanese type 2 diabetic patients.Materials and MethodsA total of 113 incident cancers including 35 cancers whose incidence was reported to be increased by obesity (27 colorectal cancers, two breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…A study from Japan could not find an association between BMI and all obesity-related cancers. 6 However, this was a study that included 2334 patients of whom only 35 patients developed cancer during follow-up. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Japan could not find an association between BMI and all obesity-related cancers. 6 However, this was a study that included 2334 patients of whom only 35 patients developed cancer during follow-up. 6 …”
Section: Discussionmentioning
confidence: 99%
“…One previous study did not find an association between BMI and obesity-related cancers in T2D. 6 Another study investigated this association with colon cancer and found only a significant relationship in patients who suffered from obesity for a total duration of 4 years or more. 7 …”
Section: Introductionmentioning
confidence: 95%
“…However, the study did not include patients with BMI less than18.5 kg/m 2 . A study based on the Japan National Center Diabetes Database did not find a significant association between BMI categories and the risk of overall cancers and obesity-related cancers among male patients, but observed a significantly higher risk of overall cancer among female patients with BMI less than 22 kg/m 2 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the association of BMI with cancer risk among T2DM patients is another approach to better understanding the mechanisms that link obesity and diabetes with cancers. However, limited evidence is available on the association between BMI and cancer risks in patients with T2DM [ 19 , 20 ]. In this study, we conducted a large-scale retrospective cohort study based on the diabetes management database in Minhang district of Shanghai, China, to examine the association between BMI and risks of overall and site-specific cancers in Chinese diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the visceral adipose tissue may be more closely associated with CRC 25,26 . A recent study from Japan has also shown no significant association between BMI and risk of CRC 27 . This implies that waist circumference may be more important than BMI as a risk factor of CRC in Asian population.…”
Section: Discussionmentioning
confidence: 99%